Identification of Novel Bioactive Compounds, Neurosporalol 1 and 2 from an Endolichenic Fungus, Neurospora ugadawe Inhabited in the Lichen Host, Graphis tsunodae Zahlbr. from Mangrove Ecosystem in Puttalam Lagoon, Sri Lanka - Maduranga, H.A.K.; Weerasinghe, W.R.H.; Attanayake, R.N.; Santhirasegaram, S.; Shevkar, C.D.; Kate, A.S.; Weerakoon, G.; Samanthi, K.A.U.; Kalia, K.; Paranagama, P.A. (Asian Journal of Chemistry, 2021)
Endolichenic fungi (ELF) have been recognized as a promising source of bioactive secondary metabolites. Sri Lanka, a biodiversity hotspot, harbours a remarkable diversity in mangrove ecosystems. In the present study, endolichenic fungi obtained from mangrove lichens of Puttalam lagoon were studied for their secondary metabolites. An endolichenic fungus, Neurospora ugadawe, isolated from the lichen host Graphis tsunodae Zahlbr. was identified up to the species level. Secondary metabolites of N. ugadawe were extracted into ethyl acetate and crude extract showed promising antioxidant and anti-inflammatory activities. Bioassay guided separation on silica gel column chromatography and preparative TLC were performed to isolate the bioactive pure compounds. Two novel bioactive pure compounds were identified as Neurosporalol 1 and Neurosporalol 2. Neurosporalol 1 showed the highest antioxidant activity compared with the positive control BHT. Further, this compound showed very low anti-inflammatory activity compared to that of the positive control aspirin. Neurosporalol 2 showed comparable antioxidant and moderate anti-inflammatory activities.